Engaging Men in Intimate Partner Relationship Programs: Service Provider and Stakeholder Perspectives. Issue 2 (March 2023) - Sharp, Paul; Coroiu, Adina; Rice, Simon M.; Seidler, Zac E.; Kealy, David; Ogrodniczuk, John S.; Oliffe, John L.
Men's intimate partner relationship services have focused on correcting the behaviors of male perpetrators of intimate partner (IPV) and/or domestic violence (DV). There is a need to advance IPV and DV prevention efforts by better equipping men with relationship skills. This study explores service providers' and stakeholders' perspectives about the challenges and strategies for assisting men to build better intimate partner relationships. Interviews were conducted with participants ( n = 30) from Canada and Australia who worked in the men's intimate partner relationships sector. Three themes were inductively derived: (a) crisis management (barriers to engagement), (b) owning deficits and leveraging strengths (engaging though accountability and action), and (c) me then we (self-work as requisite for relationship success). Using a gender relations lens, we examined the influence of masculinities on men's intimate partner relationships and engagement with services. Participants described crisis management challenges for men accessing services including shame, threats to masculine identity, and mental health challenges. Owning deficits and leveraging strengths hinged on men's accountability and action, rather than assigning blame for problematic behaviors in accessing services. Related to this, the me then we theme highlighted men's strength-based approaches in focussing on self-work to develop tangible skills and awareness needed to build healthy relationships. Overall, the findings indicate men's healthy relationships hinged on working with masculine identities to inform their perspectives and behaviors. Men's intimate partner relationship work likely requires labor at multiple levels (e.g., individual, partners, and systems) to secure the strong potential for reframing masculine identities as asset-building for men's relationships.